Gehen die Dorscherträge in der Ostsee zurück? - Thurow, F. (1973)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010